2020
DOI: 10.1371/journal.pone.0235377
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity blood flow restriction calf muscle training leads to similar functional and structural adaptations than conventional low-load strength training: A randomized controlled trial

Abstract: The purpose of this study was to investigate whether a six-week, twice weekly resistance training (4 sets at 30% 1-RM until failure) with practical blood flow restriction (BFR) using 7cm wide cuffs with a twist lock placed below the patella is superior to training without BFR (NoBFR) concerning muscle mass and strength gains in calf muscles. A two-group (BFR n = 12, mean age 27.33 (7.0) years, training experience 7.3 (7.0) years; NoBFR n = 9, mean age 28.9 (7.4) years, training experience 7.1 (6.6) years) rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 42 publications
0
29
0
2
Order By: Relevance
“…Two case reports investigated BFRT with tendon ruptures, one on biceps tendon rupture (Wentzell, 2018 ) and one on Achilles tendon rupture (Yow et al, 2018 ). Eight studies investigated the effects of BFRT on healthy tendons, five on the Achilles tendon, including four RCTs (Centner et al, 2019b ; Chulvi-Medrano et al, 2020 ; Gavanda et al, 2020 ; Picon-Martinez et al, 2021 ) and one cross-sectional study (Canfer et al, 2021 ), one RCT on the patellar tendon (Centner et al, 2021 ), one RCT on the supraspinatus tendon (Brumitt et al, 2020 ), and one cohort study on the patellar tendon (Kubo et al, 2006 ). The sample sizes of included studies ranged from 1 to 56, with only 12 participants in total for tendon pathologies out of a total of 292 participants, with most included participants having healthy tendons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two case reports investigated BFRT with tendon ruptures, one on biceps tendon rupture (Wentzell, 2018 ) and one on Achilles tendon rupture (Yow et al, 2018 ). Eight studies investigated the effects of BFRT on healthy tendons, five on the Achilles tendon, including four RCTs (Centner et al, 2019b ; Chulvi-Medrano et al, 2020 ; Gavanda et al, 2020 ; Picon-Martinez et al, 2021 ) and one cross-sectional study (Canfer et al, 2021 ), one RCT on the patellar tendon (Centner et al, 2021 ), one RCT on the supraspinatus tendon (Brumitt et al, 2020 ), and one cohort study on the patellar tendon (Kubo et al, 2006 ). The sample sizes of included studies ranged from 1 to 56, with only 12 participants in total for tendon pathologies out of a total of 292 participants, with most included participants having healthy tendons.…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes of included studies ranged from 1 to 56, with only 12 participants in total for tendon pathologies out of a total of 292 participants, with most included participants having healthy tendons. All included studies investigated the effects of a LL-BFRT intervention, five in isolation (Sata, 2005 ; Wentzell, 2018 ; Yow et al, 2018 ; Cuddeford and Brumitt, 2020 ; Skovlund et al, 2020 ) four compared with LL-RT (Brumitt et al, 2020 ; Chulvi-Medrano et al, 2020 ; Gavanda et al, 2020 ; Canfer et al, 2021 ), three compared with HL-RT (Kubo et al, 2006 ; Centner et al, 2019b , 2021 ), and one with both LL-RT and HL-RT (Picon-Martinez et al, 2021 ). The duration of BFRT interventions ranged from a single session to 14 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the study designs employed comparing failure to non-failure work-matched protocols, a favorable adaptation profile was consistently observed in the HF-BFR condition compared to the low-intensity control condition (Table 2). Therefore, it is unknown whether the positive adaptations observed is a specific effect of BFR or the product of comparing failure-to non-failure exercise given longitudinal studies have shown similar musculoskeletal benefits when low-intensity exercise is performed to failure with-and without BFR in the upper and lower limbs [50,51] as well as when comparing non-failure BFR to failure BFR protocols [52].…”
Section: Specific Resistance Training Major Limitations/areas Of Concernmentioning
confidence: 99%
“…The authors additionally used an ultrasound system to ensure that the arterial blood flow was not occluded at this pressure. This technique was later used in a few studies [ 39 , 40 ]. Despite the precautions used by the authors, this technique has some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…In analyzing muscle damage, Wilson et al [ 19 ] demonstrated that soreness, power and muscle swelling were similar between low-load resistance exercise with and without pBFR; in addition, Behringer et al [ 38 ] demonstrated that after 6 weeks of sprint training, the heart-type fatty acid-binding protein (h-FABP) was significantly lower in the group that trained with pBFR than in the control group, with similar responses between groups regarding cortisol. Additionally, studies have found similar acute pain responses between low-load resistance exercise with and without pBFR [ 26 , 40 ]; furthermore, the high-load resistance exercise induces greater pain scores than low-load resistance exercise with pBFR [ 26 ]. Considering cardiovascular events, studies have compared high-load resistance exercise with low-load resistance exercise with pBFR, noting that post-exercise acute responses are similar between the exercise protocols, in relation to autonomic modulation [ 25 ], as well as on arterial stiffness and brachial systolic or diastolic blood pressure [ 24 ].…”
Section: Introductionmentioning
confidence: 99%